Responsible Vouchering in Turtle Research : An Introduction and Recommendations - Lehn, C.; Das, I.; Forstner, M.R.J; Brown, R. (Chelonian Research Foundation, 2007)
Voucher specimens are critical to the advancement of research efforts on turtles, and by association, for conservation efforts associated with this group. This paper addresses the importance of voucher specimens and provides recommendations for responsible practices associated with voucher specimens